New insights into the cellular temporal response to proteostatic stress - Rendleman, Justin; Cheng, Zhe; Maity, Shuvadeep; Kastelic, Nicolai; Munschauer, Mathias; Allgoewer, Kristina; Teo, Guoshou; Zhang, Yun Bin Matteo; Lei, Amy; Parker, Brian; Landthaler, Markus; Freeberg, Lindsay; et al. (eLife, 2018)
Maintaining a healthy proteome involves all layers of gene expression regulation. By quantifying temporal changes of the transcriptome, translatome, proteome, and RNA-protein interactome in cervical cancer cells, we systematically characterize the molecular landscape in response to proteostatic challenges. We identify shared and specific responses to misfolded proteins and to oxidative stress, two conditions that are tightly linked. We reveal new aspects of the unfolded protein response, including many genes that escape global translation shutdown. A subset of these genes supports rerouting of energy production in the mitochondria. We also find that many genes change at multiple levels, in either the same or opposing directions, and at different time points. We highlight a variety of putative regulatory pathways, including the stress-dependent alternative splicing of aminoacyl-tRNA synthetases, and protein-RNA binding within the 3’ untranslated region of molecular chaperones. These results illustrate the potential of this information-rich resource.
Keywords: proteostasis; unfolded protein response; energy metabolism; stress response; translation regulation; central dogma